2019
DOI: 10.1093/jas/skz284
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of dietary supplementations with sodium butyrate, medium-chain fatty acids, and n-3 polyunsaturated fatty acids in late pregnancy and lactation on the reproductive performance of sows and growth performance of suckling piglets

Abstract: This study was conducted to compare the effects of adding sodium butyrate (SB), medium-chain fatty acids (MCFAs), or n-3 polyunsaturated fatty acids (n-3 PUFAs) to the diet of sows during late gestation and lactation on the reproductive performance of sows and the growth performance and intestinal health of suckling piglets. Twenty-four sows (Landrace × Large-White hybrid; third parity; 200 ± 15 kg) were randomly assigned to receive 1 of 4 diets: basal diet (control group), basal diet + 1 g SB/kg (SB group), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 56 publications
5
52
1
Order By: Relevance
“…However, the IgM has significantly increased in the MSB‐supplemented diet compared to control group. These observations are similar to the previous findings (Chen et al., 2019; Fang et al, 2014). In current study, there is no significant difference among all groups in the serum cholesterol contents, as previously reported by Ebrahimi et al.…”
Section: Discussionsupporting
confidence: 93%
“…However, the IgM has significantly increased in the MSB‐supplemented diet compared to control group. These observations are similar to the previous findings (Chen et al., 2019; Fang et al, 2014). In current study, there is no significant difference among all groups in the serum cholesterol contents, as previously reported by Ebrahimi et al.…”
Section: Discussionsupporting
confidence: 93%
“…Increased daily intake of 4 g of mixed omega-3 PUFAs (DHA and EPA) significantly increased the density of bacteria that are known to produce butyrate. Butyrate-producing bacteria play a key role in maintaining human gut health by degrading nonfermentable dietary transfer into short-chain fatty acids (SCFAs), such as butyrate [ 44 , 45 ].…”
Section: Omega-3 Pufas and The Gut Microbiotamentioning
confidence: 99%
“…Coconut oil is a rich, natural source of MCFA [29]. MCFA, which are a good feed supplement for piglets, are not frequently used in sow feeding; however, Chen et al [3] reported that MCFA fed to sows during late pregnancy and lactation shortened the weaning-to-estrus interval, reduced the incidence of diarrhea in suckling piglets, and increased the protein, IgA, IgG, and IgM content in colostrum. Supplementation with coconut oil increased the content of MCFA, mainly lauric acid, in milk, but there was no significant difference in the number of piglets born or in their mean body weight.…”
Section: Effect Of Oils In Maternal Feeding On the Sows Reproductive mentioning
confidence: 99%
“…However, there was a tendency for salmon oil to decrease piglet mortality as well as increase sow milk yield and change the milk fatty acids profile. Dietary supplementation of sows with polyunsaturated fatty acids n-3 (PUFA n-3) affects the colostrum composition to the greatest extent by increasing the content of fat and protein, while medium-chain fatty acids (MCFA) additive shortens the weaning-to-estrus interval of sows [3]. However, with regard to offspring, these authors observed more positive effect on intestinal health and lower mortality of suckling piglets when dietary sodium butyrate was used for pregnant sows compared to the results observed for dietary MCFA or PUFA n-3.…”
Section: Introductionmentioning
confidence: 99%